Understanding and Implementation of Islamic Law: Study of the Unrecorded Polygyny Phenomenon in Karawang Regency - Kasja Eki Waluyo; Rachmat Syafe’i; I Nurol Aen; Beni Ahmad Saebani (International Journal Ihya' 'Ulum al-Din, 2024)
The practice of polygamy is still a polemic to this day, with pros and cons both from human rights activists and from polygamy practitioners themselves. This research aims to examine the phenomenon of polygyny in Karawang Regency from the perspective of Islamic law and laws for justice; the social conditions that occur in Karawang further impact family welfare, such as household harmony, economic conditions, early marriage, and even polygamy. Polygamy has increased in Karawang in the form of polygyny. A lack of understanding about fairness in polygynous marriages in Karawang society supports the problems that arise from the occurrence of polygyny. The approach used in this research is an empirical juridical approach, or field research, examining applicable legal provisions and what happens in society. The results of the research show that the understanding of husbands and wives who practice polygyny in Karawang regarding Law No. 1 of 1974 regarding marriage varies, and some need help understanding the law, especially those relating to polygynous marriages. Some need help understanding law no. 1 of 1974, limited public understanding of Law no. 1 1974 concerning marriage is due to a lack of public interest. Also, because socialization regarding this law is uneven, especially regarding polygynous marriages, the public is more interested in using Islamic law.